2022
DOI: 10.36928/jpkm.v14i1.893
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Employee Engagement, Spiritualitas Kerja, Budaya Organisasi Terhadap Kinerja Karyawan Dimoderasi Kepemimpinan Kepala Sekolah

Abstract: Sekolah merupakan lembaga pendidikan yang berorientasi pada siswa sebagai pusat layanan. Segala sumber daya diarahkan untuk memberikan layanan yang optimal pada siswa dalam proses pembelajaran. Oleh karena itu, kinerja karyawan (guru dan tenaga kependidikan) di sekolah perlu ditingkatkan. Penelitian ini bertujuan untuk mengetahui pengaruh employee engagement, spiritualitas kerja, dan budaya organisasi terhadap kinerja karyawan dengan kepemimpinan kepala sekolah sebagai variabel moderasi. Populasi dalam penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The findings support the importance of organizational learning in enhancing employee competence within the local government administration. Organizational learning refers to the institution or organization's ability to engage in continuous learning activities, share knowledge, and apply acquired knowledge for the advancement of the organization [14]. By fostering a culture of continuous learning and knowledge sharing, organizations can create an environment that encourages employees to constantly improve their competencies [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings support the importance of organizational learning in enhancing employee competence within the local government administration. Organizational learning refers to the institution or organization's ability to engage in continuous learning activities, share knowledge, and apply acquired knowledge for the advancement of the organization [14]. By fostering a culture of continuous learning and knowledge sharing, organizations can create an environment that encourages employees to constantly improve their competencies [15].…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the government of Gorontalo City, a learning organization plays a crucial role in enhancing the competence of its employees. It fosters a culture of continuous learning, innovation, and knowledge sharing [14]. By creating an environment that values and promotes learning, the organization encourages employees to actively seek new knowledge, acquire new skills, and adapt to changes in their roles and responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang dilakukan oleh (Frimayasa et al, 2019;Prayoga & Yuniati, 2019;Dunggio, 2020;Putra et al, 2023) hasil penelitiannya menunjukan bahwa budaya organisasi berpengaruh positif dan signifikan terhadap kinerja karyawan. Namun beberapa peneliti dalam penelitiannya membuktikan bahwa budaya organisasi tidak berpengaruh terhadap kinerja karyawan, seperti penelitian (Asmara & Widanaputra, 2017;Kiki et al, 2023;Andriprianto & Herry Maridjo, 2022).…”
Section: Pendahuluanunclassified
“…Various studies (Ainanur & Tirtayasa 2018;Andriprianto & Maridjo, 2022;Aryani, et al, 2021) found that organizational culture has a positive and significant effect on employee performance. However, research reported by Nasir (2020) claims that organizational culture has no effect on employee performance.…”
Section: Stabilitymentioning
confidence: 99%
“…Therefore, the role of organizational culture in influencing employees to complete their work and carry out their obligations to the company becomes very important. Several previous studies (Ainanur & Tirtayasa 2018;Andriprianto & Maridjo, 2022;Aryani, et al, 2021) stated that organizational culture has a positive and significant effect on employee performance. However, Nasir (2020) believes that organizational culture has no effect on employee performance .…”
Section: Introductionmentioning
confidence: 98%